NURSING CARE FOR MPOX PATIENTS: PREVENTION, CONTROL, AND REHABILITATION - Visaratanunta, Phudsadee; Thongchan, Wichidtra (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
Mpox (Monkeypox) is a viral infectious disease that can be transmitted from animals to humans, as well as from person to person. Although the mortality rate of Mpox is lower than that of smallpox, the increasing number of outbreaks in many countries has underscored the need for effective patient care management. Nurses play a crucial role in the prevention, control, and rehabilitation of patients to limit transmission and reduce the impact of the disease. This article focuses on nursing care guidelines for Mpox patients in three main aspects: 1) Prevention - Focusing on emphasizing public education on reducing the risk of infection; implementing infection control measures in healthcare settings, such as the proper use of personal protective equipment (PPE), hand hygiene, and vaccination for high-risk groups. 2) Control - Focusing on highlighting the importance of early screening and diagnosis; isolating patients to prevent further transmission, providing symptomatic treatment to reduce disease severity, and preventing possible complications such as secondary bacterial infections or dehydration. 3) Rehabilitation - Focusing on providing holistic care that addresses physical, psychological, and social needs of patients. This includes promoting skin wound healing and offering psychosocial support to alleviate stress and anxiety in both patients and their families.